1991
DOI: 10.1002/gcc.2870030111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cytogenetic analysis of tumors in von recklinghausen neurofibromatosis

Abstract: Von Recklinghausen neurofibromatosis (NF1) is a common autosomal dominant disorder mapped to 17q11.2 and typically characterized by the occurrence of neural crest-derived tumors. The gene has recently been cloned using reverse genetics or "positional cloning" approaches. Its function, however, remains unknown. We have performed cytogenetic and molecular analyses on 9 malignant tumors from NF1 patients to look for loss of alleles or chromosome rearrangements involving chromosome 17 to test the hypothesis that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 26 publications
6
82
1
1
Order By: Relevance
“…Both malignant (Glover et al, 1991;Menon et al, 1990;Skuse et al, 1989;Xu et al, 1992) and benign tumors (Colman et al, 1995;Sawada et al, 1996;Serra et al, 1997) in NF1 have been associated with somatic loss of the second, wild-type NF1 allele. However, studies of CALMs have not found evidence of lesional loss of the second allele (Eisenbarth et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Both malignant (Glover et al, 1991;Menon et al, 1990;Skuse et al, 1989;Xu et al, 1992) and benign tumors (Colman et al, 1995;Sawada et al, 1996;Serra et al, 1997) in NF1 have been associated with somatic loss of the second, wild-type NF1 allele. However, studies of CALMs have not found evidence of lesional loss of the second allele (Eisenbarth et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with CGH analysis, the karyotype of NFl-associated MPNST-derived cells are complex with chromosomal numbers ranging from 34-270 indicative of hypodiploidy, hypotriploidy, hypotetraploidy and hypertriploidy and hypertetraploidy (109,116,125 and references therein). While breakpoints were frequent, a common specific breakpoint was not detected.…”
Section: Somatic Alterations In Nfl-associated Mpnstmentioning
confidence: 63%
“…Whether other cellular components of neurofibromas show cytogenetic abnormalities is unclear. Some neurofibroma fibroblastlike derived cultures were reported to show an increased frequency of chromosomal aberrations (108), while others were typically negative (109).…”
Section: Somatic Alterations That May Modify Neurofibromagesismentioning
confidence: 99%
“…The homozygous inactivation of NFl in NFl-associated MPNST, first reported by Skuse et al (60), has been confirmed in about 50% of tumors (n=22) by LOH (67,109,112,114,115). Mutations in both NFl alleles have been identified in a single MPNST (114).…”
Section: Genetics Of Mpnst Developmentmentioning
confidence: 87%